How is the SelfCare Management of Patients with Type II Diabetes Mellitus ?- Characteristics and Knowledge - Iriana, Pramita (Asian Journal of Pharmaceutical Research and Development, 2022)
Background: Diabetes mellitus is a long-term disease characterized by increased blood sugar levels. The number of people with diabetes mellitus in Indonesia continues to increase from year to year. Diabetes control can be done with self care management which can be influenced by the characteristics of diabetics, knowledge, attitudes and behavior. Objective: To find out about the relationship between characteristics and knowledge with self care management in patients with type II diabetes mellitus. Research Methods: Quantitative research with analytical descriptive type and using a cross sectional approach. The population of this study was all patients with type II diabetes mellitus in the Kemyoran District Health Center aged 45 years and over with a sample of 93 respondents and using purposive sampling technique. The instrument used was a questionnaire and analyzed using the Chi-Square test. Results: In this study, the results of the Chi-Square test showed that the variables of age (p=0.013), gender (p=0.764), education (p=0.003), duration of diabetes mellitus (p=0.012) and knowledge (p= 0.005 Conclusion: there is a relationship between age, education, duration of diabetes mellitus and knowledge with self care management of patients with type II diabetes mellitus.